CODE MIXINGS USED BY BEAUTY VLOGGERS - Ni Kadek Dinda Saraswati; I Wayan Suarnajaya; I Nyoman Adi Jaya Putra (Undiksha Press, 2022)
This study aimed to know the types of code-mixing often used and the reasons for using code-mixing by the beauty vloggers in their videos. Mix methods (qualitative-quantitative) methods are used in this study and focused on qualitative rather than the quantitative approach. This research focused on the phenomenon of code-mixing between Indonesian and English used by beauty vloggers in their videos. Moreover, the data were collected by observing the beauty vloggers' video and interviewing the selected beauty vloggers using the google form. Furthermore, the data obtained were analyzed using the theory of Hoffman (1991), Ho (2007), and Saville-Troike (1986). Based on the data analysis, the result showed that the dominant type of code-mixing used by the beauty vloggers was Intra-sentential code-mixing with a total number of 122 items (59%). Meanwhile, the principal reason underlying code-mixing by beauty vloggers is